Efforts to Improve Science Learning Results About Health Disorders in Blood Circular Organs Using IT-Based Media - Lisfaatun, Lisfaatun (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in science muple at SD IT Robbani Kendal class VA by using IT-based media. This Classroom Action Research was carried out in three cycles consisting of: planning, implementing, observing and reflecting. In the first cycle, the students who completed the post test were 62.5%. In the second cycle students who completed after carrying out the post test were 87.5%. In cycle III students who completed after carrying out the post test were 96%. These results indicate that IT-based media can improve student learning outcomes,especially science class VA muple at SD IT Robbani Kendal.